Exploring future food security, livelihoods and environments under climate change in South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
In June 2013, the CGIAR program on Climate Change, Agriculture and Food Security organised a workshop at Nagarkot, Nepal with expert-stakeholders from Bangladesh, India, Nepal, Pakistan and Sri Lanka, as well as international experts to explore the future of food security, livelihoods and environments in South Asia under conditions of climate change. Scenarios are the "what if" questions to which decision makers need answers. They articulate plausible future development pathways in detail. Policy makers need credible, science-based scenarios now about the possible trajectories their countries could take in the future, in order to create climate-resilient societies and economies. Participants in the South Asia scenarios process worked hard together to ensure the usefulness of the alternate future contexts for decision-makers. They also developed new links between their sectors and organizations. Going forward, CCAFS will merge the regional scenarios with the IPCC's climate change scenarios. The consolidated scenarios will help guide public decision-making. They will also be useful for private decision-makers to target investments, and research and development areas. The scenarios will also provide indicators, enabling decision makers to judge how development trajectories are changing.